Heteropoly Acid/Carbon Nanotube Hybrid Materials as Efficient Solid‐Acid Catalysts. Issue 9 (30th July 2014) - Qi, Wei; Liu, Wei; Liu, Songyun; Zhang, Bingsen; Gu, Xianmo; Guo, Xiaoling; Su, Dangsheng
Abstract A prototype supported solid‐acid catalyst composed of a heteropoly acid (HPA) and nitrogen‐functionalized carbon nanotubes (NCNT) has been developed. The chemical structure and acid strength of the HPA/NCNT hybrid have been characterized thoroughly by IR spectroscopy, X‐ray photoelectron spectroscopy, TEM, and titration measurements. NCNT supports provide the HPA with an ideal hydrophobic environment, which could prevent the deactivation of the acid sites effectively in aqueous media. HPA/NCNT hybrid catalysts tend to adsorb and enrich hydrophobic substrates (ester) and release the product with high polarity (ethanol) in the aqueous phase, and this synergistic effect facilitates the catalytic process and enhances the activity of HPAs for ester hydrolysis reactions. The HPA and NCNT combine through electrostatic interactions, which ensures the relatively high stability and easy regeneration of the HPA/NCNT hybrid catalysts. The present approach provides a promising and universal strategy for the construction of hybrid catalysts based on HPA and nanocarbon with unique acidic or redox properties.